Quality of mango (Mangifera indica 'Carabao') grown in farms subjected to site-specific pest management strategies - Bayogan, Emma Ruth V.; Esguerra, Elda B.; Opina, Oscar S.; Campeon, Rogelio T. (2012)
The 'Carabao' mango, a commercially important fruit crop, is prone to attacks of pests snd diseases in all stages of development. The judicious use of pesticides must often be complemented with other control measures. Site-specific pest management program were drawn for three mango farms in Mati, Davao Oriental, Philippines. These included calendar spraying, no bagging, bagging (with or without insecticide-impregnated plastic strips), and pesticide spray decision tool. The mango leafhopper population was controlled while panicle and blossom blight was slight in the three farms. Yields did not statistically vary. Foliar application tended to improve yields while bagging with insecticide-impregnated plastic strips reduced scale/mealy bug damage in farm 2. In farm 1, no yield increase was noted when a second application of flower inducer was done. Increases in percentages of grade 1 fruit as well as reductions in rejects were distinctly exhibited in harvested produce from the three farms. Size quality profile of two farms showed increases in percentage of medium or large fruit while another farm showed a reduction in super small fruit. Prevalent quality defects observed were misshapen, scab, undersized, windscar, and veins. Postharvest infection due to anthracnose was slight while stem end rot was nil. Visual quality and shelf life appeared better in fruit harvested from trees protected from pests using spray decision tool and bagging. Further, the reduction in pesticide costs ranged from 4% to 42%.
Keywords: Mango; Fruit diseases and pests; Integrated Pest Management